Medical Device Development: the challenge for ergonomics - Martin, Jennifer L.; Norris, Beverley J.; Murphy, Elizabeth; Crowe, John A. (Elsevier, 2008)
High quality, well designed medical devices are necessary to provide safe and effective clinical care for patients as well as to ensure the health and safety of professional and lay device users. Capturing the user requirements of users and incorporating these into design is an essential component of this. The field of ergonomics has an opportunity to assist, not only with this area, but also to encourage a more general consideration of the user during medical device development. A review of the literature on methods for assessing user requirements in engineering and ergonomics found that little published work exists on the ergonomics aspects of medical device development. In particular there is little advice available to developers on which issues to consider during design and development or recommendations for good practice in terms of the methods and approaches needed to capture the full range of user requirements. The Multidisciplinary Assessment of Technology Centre for Healthcare (MATCH) is a research collaboration that is working in conjunction with industrial collaborators to apply ergonomics methods to real case study projects with the ultimate aim of producing an industry-focused guide to applying ergonomics principles in medical device development.